Impact of different housing densities combined with Environmental enrichment on the production of Japanese quail - Vieira, Marcílio José; Mendonça, Michele de Oliveira; Valentim, Jean Kaique; Toledo, Damares de Castro Fidélis; Oliveira, Steferson dos Reis; Borges, Samuel Oliveira (Acta Scientiarum. Animal Sciences, 2024)
This study evaluated the zootechnical performance, egg quality, and behavior of Japanese quails in the laying phase housed in cages of different densities and with or without environmental enrichment. A total of 224 quail were used and distributed into two groups: one with a housing density of 122.7 cm2 bird-1 and one with a housing density of 157.8 cm2 bird-1, each with and without environmental enrichment. The results showed that environmental enrichment did not influence the zootechnical performance parameters of the quail. However, housing density independently affected performance, except for egg mass and bird viability. A lower density (157.8 cm2 bird-1) resulted in greater specific egg weight, albumen percentage, and shell thickness. The interaction between density and environmental enrichment revealed that eggs from quail housed at higher density without enrichment had a greater yolk percentage, while quails housed at lower density without enrichment had a greater shell percentage. The tonic immobility time of the quails was not affected by treatment with different densities or environmental enrichment agents. It can be concluded that a lower housing density, with seven quail per cage (157.8 cm2 bird-1), regardless of environmental enrichment, provides better zootechnical performance and egg quality.